Exploring the Relationship between Perceived Multidimensional Social Support and Well-Being among Community Seniors Participating in Group Exercise Programs - Hooi, Lim Boon; Yau, Yi; Shen, Ya Chun; Lee, Kam-Fong; Raj, Abel (International Journal of Statistics in Medical Research, 2025)
This study examines the relationship between perceived multidimensional social support and well-being among community-dwelling seniors engaged in group exercise programs, aiming to address a gap in the current literature. A total of 162 older adults from two communities in Selangor, Malaysia, participated in structured group exercise sessions. Using a quantitative survey design, data were collected through the Multidimensional Scale of Perceived Social Support (MSPSS) and the BBC Well-Being Scale to assess perceived support and overall well-being, respectively. Community leaders were engaged to support the study’s approval and facilitate its implementation. Descriptive statistics were used to summarize participants’ demographic characteristics and study variables, while Pearson correlation analysis was conducted to examine the relationships between perceived social support and well-being. The sample consisted predominantly of males (63%), reflecting a gender imbalance in exercise participation that aligns with findings from previous studies. Results showed no significant correlation between perceived social support and overall well-being (r(160) = -0.113, p > .05), indicating a weak negative relationship. This suggests that higher levels of perceived social support did not correspond with notable improvements in well-being among the participants. These findings challenge the prevailing literature that often highlights a positive association between social support and well-being, suggesting that the relationship may be more nuanced within the context of community-based group exercise programs for older adults. Further investigation is needed to uncover the underlying factors that may influence this relationship in this specific demographic.